Desain Agrowisata Nanga-Nanga Di Kota Kendari Dengan Pendekatan Arsitektur Organik - Fik, Muh. Taufik; Nahdatunnisa, Nahdatunnisa; Ahyarky Abidin, Afri (Architectura : Journal of Architecture and Planning, 2025)
Agrotourism is one of the strategies for sustainable tourism development that integrates agricultural, educational, and recreational functions within a single area. Kendari City has great potential through the Nanga-Nanga area, which is rich in natural resources and agricultural land, but has not yet been optimally utilized as a tourist destination. This study aims to design the concept of Nanga-Nanga agrotourism using an organic architecture approach that emphasizes harmony between buildings and the environment. The research methods used include literature studies, field observations, and site analysis to identify the potentials and constraints of the area. The design results show that the application of organic architectural principles produces a design that is adaptive to natural conditions, uses local materials, and blends with the surrounding agricultural and natural landscape. Thus, the results and discussions collected can be concluded and formulated into a conceptual basis for planning and design. The development of the Nanga-Nanga Agrotourism is expected to provide positive value for the local community and increase the attractiveness for tourists.